Broad spectrum integration of climate change in health sciences curricula - Ogunseitan, Oladele A. (Frontiers in Public Health, 2022)
In response to a University of California systemwide initiative to expand the knowledge base of climate change, two half-day workshops were held for faculty in the College of Health Sciences at the UC Irvine. In the first workshop, 20 participants who teach in the Schools of Nursing, Medicine, Pharmacy, and Pharmaceutical Science, or the Program in Public Health convened to explore concepts of sustainability, theoretical models of curriculum integration, challenges to adding new competencies into professional training, and strategies for integrating climate change modules and case studies into the curricula. The second half-day workshop was held a year after the first workshop to review how faculty members have modified their syllabus to integrate climate change information with varying degrees of success. A case study is presented regarding an asynchronous fully online course Introduction to Global Health, which is open to enrollment by students from all campuses of the University of California. The outcomes revealed preferential adoption of models of curriculum integration which minimized disruption of the sequence of topics in pre-existing courses. These include, for example, the use of longitudinal climate datasets for quantitative analysis of disease outcomes, and description of episodic events involving extreme weather conditions to explore differences in social determinants of vulnerability to climate change impacts in different populations. Integration of climate change as a distinct topic seems easier in elective courses in comparison with required courses designed to cover pre-established professional knowledge, competencies, and skills. The emergent requirement for interprofessional training in the health sciences provides an opportunity for the development of a cross-cutting competency domain including climate change as a unifying theme in a stand-alone course or set of courses in a sequenced model of curriculum integration.